Analisis Penggunaan Konjungsi Kronologis dan Konjungsi Kausalitas pada Teks Berita di Tribunjatim.com Edisi Febuari 2025 sebagai Sumber Pemahaman Mengenai Konjungsi pada Pembelajaran Bahasa Indonesia - Olivia Ramadhani, Chelsea; Cahya Salsabila, Fadla; Dihas Saputri, Tiara; Ari Yani, Riska; Anggita Purnami, Rahma; Purwo Yudi Utomo, Asep; Luriawati Naryatmojo, Deby; Buana Dewi Islamy, Amilia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the use of chronological conjunctions and conjunctions of causality in the news text in TribunJatim.com February 2025 edition. Chronological conjunctions are used to express the sequence of time in an event, while the conjunction of causality connects the causal relationship in sentences. The analysis was carried out by qualitative descriptive method, with data collection techniques in the form of news text documentation published during that period. The results showed that the use of chronological conjunctions was more dominant in narrative news, while causality conjunctions were found in many news and opinion news. This finding is expected to be a reference in learning Indonesian, especially in understanding the role of conjunctions in written discourse. The method used is qualitative descriptive, with data collection through documentation of news texts published during the specified period. The analysis involves identifying the types of conjunctions, their functions, and the accuracy of their usage within the context of the news. The results show that chronological conjunctions are more dominantly found in narrative news that tells a sequence of events in order, while causal conjunctions are more frequently used in analytical and opinion news that emphasize cause-and-effect relationships. These findings provide a clear empirical overview of the patterns of conjunction usage in online news texts. This study is expected to serve as an important reference in Indonesian language learning, especially in understanding the role and function of conjunctions in constructing cohesive and communicative written discourse.